Mental Health Support Program for Adolescents at SMK Mardhika: Program Dukungan Kesehatan Mental pada Remaja di SMK Mardhika - Anna Mariani Kartasasmita; Amanda Putri Fera; Alfiyyah Sarah Farida; Rizki Setiyawan (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2026)
This mental health support program aimed to improve students’ mental health awareness and coping skills at SMK Mardhika, East Jakarta. Many students experienced stress and low motivation due to unequal treatment between classes, making the program urgent to support their emotional well-being. The school partnered by providing facilities and coordinating participants. Activities included briefing, pre-test, group counseling, psychoeducation, ice breaking, and post-test evaluation using the DASS-21 (Depression Anxiety Stress Scales) instrument. The results showed a positive change, with students in the “normal” category increasing from 51.7% to 72.4%. Participants reported feeling more confident, expressive, and emotionally balanced. The school plans to sustain this effort through peer support groups and regular counseling. The activity effectively created a more inclusive and supportive school environment.